Pandemic Pandemonium: Negotiating Identities as a Middle Grades School Parent, Doctoral Student, and High School Mathematics Teacher - Veronica Cambra-Faraci (Middle Grades Review, 2022)
This autoethnographic study represents a reflection of my experiences as a parent of middle school children, doctoral student, and mathematics high school teacher through the COVID-19 pandemic in the United States. Navigating all three identities simultaneously presented many challenges, including fear, isolation, and exhaustion; however, it also allowed me to reflect upon and transfer methods that I perceived as effective from one of my identities to one or more of my other identities. Therefore, this study investigated how reflecting upon my own funds of identity influenced my practices as a high school mathematics teacher during the COVID-19 pandemic.
Keywords: autoethnography; secondary math; COVID-19; identities; parenting